APOE-ε4 Carrier Status and Gut Microbiota Dysbiosis in Patients With Alzheimer Disease - Hou, Min; Xu, Gaolian; Ran, Maosheng; Luo, Wei; Wang, Hui (Frontiers in Neuroscience, 2021)
Background: Alternations in gut microbiota and a number of genes have been implicated as risk factors for the development of Alzheimer’s disease (AD). However, the interactions between the altered bacteria and risk genetic variants remains unclear. Objective: We aimed to explore associations of the genetic variants with gut bacteria in the onset of AD. Methods: We collected baseline data, stool and blood samples from 30 AD patients and 47 healthy controls in a case-control study. The rs42358/rs4512 (ApoE), rs3851179 (PICALM), rs744373 (BIN1), rs9331888 (CLU), rs670139 (MS4A4E), rs3764650 (ABCA7), rs3865444 (CD33), rs9349407 (CD2AP), rs11771145 (EPHA1), rs3818361/rs6656401 (CR1) were sequenced, and microbiota composition was characterised using 16S rRNA gene sequencing. The associations of gut bacteria with the risk genetics were analysed. Results: Apolipoprotein ε4 allele and rs744373 were risk loci for the AD among 12 genetic variants. Phylum Proteobacteria, order Enterobacteriales, Deltaproteobacteria and Desulfovibrionales, family Enterobacteriaceae and Desulfovibrionaceae, genus Escherichia_Shigelia, Ruminococcaceae_UCG_002, Shuttleworthia, Anaerofustis, Morganelia, Finegoldia and Anaerotrunous were increased in AD subjects, while family Enterococcaceae, genus Megamonas, Enterococcus and Anaerostipes were more abundant in controls (P < 0.05). Among the altered microbiota, APOE ε4 allele was positively associated with pathogens: Proteobacteria. Conclusion: The interaction of APOE ε4 gene and the AD-promoting pathogens might be an important factor requiring for the promotion of AD. Targeting to microbiota might be an effective therapeutic strategy for AD susceptible to APOE ε4 allele. This needs further investigation.